SARS-CoV2 infection: functional and morphological cardiopulmonary changes in elite handball players. (14th October 2021) - Fikenzer, S; Kogel, A; Hepp, P; Lavall, D; Stoebe, S T; Rudolph, U; Laufs, U; Hagendorff, A
Abstract: Background: There is increasing evidence of cardiac involvement in SARS-COV-2 infections. This may not only apply to symptomatic infections but may also affect asymptomatic athletes. This study aimed to characterize the possible acute cardiac involvement of SARS-COV-2 infection in athletes both morphologically and functionally. Methods and results: Eight elite handball players (27±3.5 y) with past SARS-COV-2 infection were retrospectively analyzed and compared with four uninfected team-mates (22±2.6 y). Athletes were examined 19±7 d after positive PCR-test. Echocardiographic assessment of the global longitudinal strain under resting conditions was not significantly changed after SARS-CoV2 infection (−17.7% vs. −18.1%) but magnetic resonance imaging showed minor signs of acute inflammation/edema in all patients (T2-mapping: +4.1ms) without reaching the Lake-Louis criteria. Spiroergometric analysis showed a significant reduction in VO2max (−292 ml/min, −7.0%), oxygen-pulse (−2.4 ml/beat, −10.4%), and respiratory minute volume (VE) (−18.9 l/min, −13.8%) in athletes with a history of SARS-CoV2 infection (p<0.05, respectively). The parameters were unchanged in the control group. Conclusion: SARS-CoV2 infection caused functional impairment of cardiopulmonary performance primarily under stress in elite athletes. It seems reasonable to screen athletes after SARS-CoV2 infection at least with spiroergometry to mark performance limitations and to ensure an optimal return to competition. FUNDunding Acknowledgement: Type of funding sources: None.